Investigation of the teaching cognition and capabilities of clinical advisers for masters degree level nursing specialty graduate students - Xiao-Lei Zhao; Shao-Yu Mou; Yan-Han Chen; Wen-Fen Zhu (Elsevier, 2014)
Purpose: To assess the culturing cognition and teaching of core capabilities of clinical advisers for masters degree level nursing graduate students in order to provide criteria for selecting and training clinical advisers, and to monitor clinical teaching quality. Methods: A questionnaire was completed by 66 nursing specialty clinical advisers. The questionnaire was divided into three sections: basic condition, culturing cognition of the nursing specialty graduate students, and self-evaluation of teaching core capabilities as measured by the Clinical Nursing Teachers Core Capabilities Graphic Rating Scale. Results: Forty-five of the surveyed advisers served undergraduate level students (68.18%), and seven of them (10.61%) had experience advising graduate nursing students. The advisers, in general, had limited knowledge regarding guidance for nursing specialty graduate students. The self evaluation total score for core capabilities teaching was (120.55 ± 7.37), containing professional capability (4.47 ± 0.34), leadership capability (4.01 ± 0.22), problem solving capability (3.89 ± 0.30), and education teaching capability (3.65 ± 0.23). The highest scored item was the capability to assess and handle a patients' condition (4.44 ± 0.56), while the lowest scored item was the capability to do scientific research (3.29 ± 0.89). Conclusion: Clinical advisers for nursing specialty graduate students in our survey were generally inexperienced with regarding to training and culturing nursing graduate students. These advisers were prepared for core teaching competency, but were not qualified to conduct scientific research. Based on these results, it would be beneficial to provide the clinical advisers more training on teaching cognition for graduate students and improve their competency to perform scientific research.